Get2PrEP: An Electronic Medical Record Laboratory Comment Increased Safe Sex Counseling But Not Preexposure Prophylaxis Services at a Large Urban Academic Medical Center in Northern Manhattan. Issue 10 (29th October 2022) - Spicehandler, Rebecca; Zucker, Jason; Yumori, Caitlin; Adan, Matthew; Carnevale, Caroline; Theodore, Deborah; Castor, Delivette; Meyers, Kathrine; Whittier, Susan; Yin, Michael T.; Cohall, Alwyn; Olender, Susan; et al.
Abstract : An interpretative laboratory comment added to positive sexually transmitted infection results in the electronic medical record may have increased HIV prevention discussions, although not HIV screening or provision of or referral to preexposure prophylaxis. Abstract : Background: HIV preexposure prophylaxis (PrEP) remains underutilized despite its efficacy and potential population impact. Achieving PrEP's full potential depends on providers who are knowledgeable and comfortable prescribing it to individuals at risk of acquiring HIV. Previous educational interventions targeting provider-related uptake barriers have had limited success. We designed and tested an electronic medical record (EMR) interpretative comment to improve the delivery of PrEP. Methods: An EMR comment provided information on PrEP eligibility and referral resources to providers delivering positive chlamydia and gonorrhea results. Positive test results for bacterial sexually transmitted infections before intervention (January 1, 2019–August 23, 2019) and after intervention (August 24, 2019–December 31, 2019) were identified. A retrospective chart review was conducted to ascertain provider documentation of PrEP discussions or provision, HIV prevention discussions, and HIV screening. Pretest-posttest analysis was performed to compare the provision of PrEP and HIV prevention services. Results: We reviewed 856 preintervention encounters spanning 8 months and 461 postencounters spanning 4 months. Patient demographics were comparable. We observed an increase in provider documentation of safe sex and condom counseling (odds ratios [ORs], 1.2 [95% confidence interval CI, 1.07–1.18] and 1.11 [95% CI, 1.05–1.17], respectively), and the absence of any HIV prevention discussion decreased (OR, 0.85; 95% CI, 0.80–0.90), but not HIV screening or PrEP documentation. Conclusions: We demonstrated that an EMR laboratory comment had a modest effect on increasing risk reduction counseling, although not HIV screening or PrEP prescriptions. Future strategies to encourage provider delivery of sexual health services may benefit from more targeted strategies that combine behavioral and information technology approaches.